Liver Histopathology of Rats Induced by High-Fat Feed After Giving Neem Leaf Ethanol Extract - Sri Isdadiyanto; Anggih Retno Pratiwi; Siti Muflichatun Mardiati (Biosaintifika: Journal of Biology & Biology Education, 2022)
Foods that contain high levels of fat can cause hyperlipidemia, which is one of the triggering factors for non-alcoholic fatty liver disease. Neem leaves contain flavonoids, alkaloids and tannins which have the ability to act as hepatoprotectors. This study aimed to determine the Liver Histopathology of Rats Induced by High-Fat Feed After Giving Neem Leaf Ethanol Extract. Twenty-four the male white rats (Rattus norvegicus L.) were divided into 6 treatment groups, namely: normal control (P0); negative control (P1: given high-fat diet); P2 treatment (P1+ 8 mg/200gBW simvastatin); and P1+ the dose of neem leaf ethanolic extract of  75; 100; and 125 mg/200gBW (P3; P4; and P5). Fixation process with 10% Neutral Formalin Buffer (NFB) solution. Liver histopathological preparations were made by paraffin method and Hematoxylin-Eosin staining, histopathological observations with a 400x magnification microscope. Liver histopathology was analyzed descriptively, homogeneous and normally distributed data of liver weight and hepatocyte diameter were analyzed statistically using ANOVA followed by Duncan's test with a significance level of 5% using SPSS 16.0 software. The results showed that the administration of ethanolic extract of neem leaves could improve the liver histology structure. From this study it was concluded that the ethanolic extract of neem leaves can be used as an alternative hepatoprotector.